Perancangan dan Pembangunan Sistem Manajemen Podcast di RKDD Desa Cemani - Sri Hariyati Fitriasih; Bayu Dwi Raharja (Redtech Putra Benua, 2024)
This community service aims to develop a podcast management system as a means of disseminating information and education in the digital community space of Cemani Village. The methods used include training, implementation of podcasting technology, and evaluation of the effectiveness of the podcast management system. The results show that this system is able to increase the accessibility of information and community participation in digital-based activities. In conclusion, the use of podcast technology can be an innovative solution to support the sustainability of digital community spaces in villages.